2020
DOI: 10.1088/2515-7639/ab749d
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties of CsPbCl3 thin films across phase transitions

Abstract: The local thermal conductivity, thermal diffusivity, and volumetric heat capacity of cesium lead chloride perovskite thin films are mapped simultaneously and with highest spatial resolution by a scanning near-field thermal microscope. Both, the 3D phase (CsPbCl 3 ) and the 0D phase (Cs 4 PbCl 6 ) are investigated. For CsPbCl 3 thin films the variation of the thermal properties across the phase transitions in the range from room-temperature to 65°C are analyzed. While the thermal conductivity at room temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 46 publications
(75 reference statements)
0
21
0
Order By: Relevance
“…49 These thermal conductivities are somewhat lower than those recently found for CsPbCl 3 thin films with large laterally extended crystallites (0.49 W (m K) À1 ). 51 Note that, since the phonon mean-free-path is also reduced by defects, thermal conductivities are lower near grain boundaries in thin films, as shown in local thermal conductivity analyses with a high spatial resolution by an AFM based technique. 50 This technique allows determining the local thermal diffusivity, aside from the local thermal conductivity; thus the local volumetric heat capacity can be calculated afterwards.…”
Section: Experimental Determination Of Thermal Propertiesmentioning
confidence: 96%
See 1 more Smart Citation
“…49 These thermal conductivities are somewhat lower than those recently found for CsPbCl 3 thin films with large laterally extended crystallites (0.49 W (m K) À1 ). 51 Note that, since the phonon mean-free-path is also reduced by defects, thermal conductivities are lower near grain boundaries in thin films, as shown in local thermal conductivity analyses with a high spatial resolution by an AFM based technique. 50 This technique allows determining the local thermal diffusivity, aside from the local thermal conductivity; thus the local volumetric heat capacity can be calculated afterwards.…”
Section: Experimental Determination Of Thermal Propertiesmentioning
confidence: 96%
“…( r) of 1.3 J cm À3 K À1 and 0.9 J cm À3 K À1 were determined for CsPbBr 3 and CsPbCl 3 at RT respectively. 50,51 The findings of these studies suggested that heat dissipation in dynamically operated halide perovskite optoelectronic devices will be very inefficient. As such, the thermal management of light-emitting diodes and lasers based on halide perovskites is a challenge and requires particular attention (see strategies to enhance the thermal properties of transport layers in perovskite devices).…”
Section: Experimental Determination Of Thermal Propertiesmentioning
confidence: 99%
“…Compared to 3D perovskites, lower κ is observed in the case of 0D perovskites such as (MA) 3 Bi 2 I 9 and Cs 4 PbCl 6 . [ 93,94,119 ] Discrete octahedra structure with low group velocities, reduced phonon lifetimes, and the localization of vibrational energy leads to the ultralow κ in 0D perovskites. [ 64,93 ]…”
Section: Thermal Transport In Halide Perovskitesmentioning
confidence: 99%
“…As a frequently used method in the fabrication of perovskite films, chemical vapor deposition (Figure 15a) was also employed in the synthesis of the dual-phase inorganic CsPbX 3 / Cs 4 PbX 6 perovskite film. [172][173][174][175][176][177] During the preparation process, it was found that the CsBr/PbBr 2 ratio was a very significant parameter in determining the PL emission intensity. [172] When the ratio was 44:16.5, the sample exhibited the highest PL efficiency (Figure 15b,d,e).…”
Section: Bulk/filmmentioning
confidence: 99%